2017
DOI: 10.1002/jor.23566
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chondrolabral mechanics, coverage, and congruency following peri‐acetabular osteotomy for treatment of acetabular retroversion: A patient‐specific finite element study

Abstract: Using a validated finite element (FE) protocol, we quantified cartilage and labrum mechanics, congruency, and femoral coverage in five male patients before and after they were treated for acetabular retroversion with peri-acetabular osteotomy (PAO). Three-dimensional models of bone, cartilage, and labrum were generated from computed tomography (CT) arthrography images, acquired before and after PAO. Walking, stair-ascent, stair-descent, and rising from a chair were simulated. Cartilage and labrum contact stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Computational modeling techniques such as finite element analysis (FEA) (Anderson et al, 2010; Harris et al, 2012; Henak et al, 2014; Henak et al, 2011; Knight et al, 2017; Zou et al, 2013) and discrete element analysis (DEA) (Abraham et al, 2013; Armiger et al, 2009; Townsend et al, 2018) have been utilized to predict hip cartilage contact stresses. The majority of these studies have investigated cartilage contact stresses when loading their computational models with walking gait data obtained directly from instrumented total hip implants (Bergmann et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling techniques such as finite element analysis (FEA) (Anderson et al, 2010; Harris et al, 2012; Henak et al, 2014; Henak et al, 2011; Knight et al, 2017; Zou et al, 2013) and discrete element analysis (DEA) (Abraham et al, 2013; Armiger et al, 2009; Townsend et al, 2018) have been utilized to predict hip cartilage contact stresses. The majority of these studies have investigated cartilage contact stresses when loading their computational models with walking gait data obtained directly from instrumented total hip implants (Bergmann et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, adding quantitative T1ρ mapping assessing the hip cartilage condition pre-and post-operatively comparing hip arthroscopy vs. no hip arthroscopy in the setting of a PAO is innovative. This is especially relevant as it has been shown using patient specific finite element modeling [74] that although a PAO favorably alters the joint mechanics at the labral-chondral junction, joint congruency is decreased which could be further impacted if the labral structure is altered with the addition of hip arthroscopy.…”
Section: Using the Results Of This Trialmentioning
confidence: 99%
“…81 A recent FEA modeling study of a small number of acetabular retroversion patients found that while PAO served to offload forces passing through the labrum during several activities of daily living and shift contact stress medially and posteriorly within the articular surface of the acetabulum, peak contact stress in these patients actually increased postoperatively. 42 While this finding presently only adds to the controversy of how best to treat individuals with this deformity, it shows the potential for computational modeling to contribute to a better understanding of the effects of different surgical procedures in these unique patient populations.…”
Section: Computational Analysis Of Joint Mechanics In Dysplasia and Amentioning
confidence: 97%
“…Focal overcoverage or under-coverage can often be better visualized on three dimensional (3D) reconstructions of the pelvis CT than on radiographs. Computational methods have been developed based on CT scans to determine potential impingement-free range of motion, [40][41][42] and cross-sectional imaging through the distal femur (CT or MRI) can be used to assess femoral version.…”
Section: Physical Examinationmentioning
confidence: 99%